Ecological Correlates of Elevational Range Shifts in Tropical Birds - Neate-Clegg, Montague H. C.; Jones, Samuel E. I.; Tobias, Joseph A.; Newmark, William D.; Şekercioǧlu, Çaǧan H. (Frontiers in Ecology and Evolution, 2021)
Globally, birds have been shown to respond to climate change by shifting their elevational distributions. This phenomenon is especially prevalent in the tropics, where elevational gradients are hotspots of diversity and endemism. Empirical evidence has suggested that elevational range shifts are far from uniform across species, varying greatly in the direction (upslope vs downslope) and rate of change (speed of elevational shift). However, little is known about the drivers of these variable responses to climate change, limiting our ability to accurately project changes in the future. Here, we compile empirical estimates of elevational shift rates (m/yr) for 421 bird species from eight study sites across the tropics. On average, species shifted their mean elevations upslope by 1.63 ± 0.30 m/yr, their upper limits by 1.62 m ± 0.38 m/yr, and their lower limits by 2.81 ± 0.42 m/yr. Upslope shift rates increased in smaller-bodied, less territorial species, whereas larger species were more likely to shift downslope. When considering absolute shift rates, rates were fastest for species with high dispersal ability, low foraging strata, and wide elevational ranges. Our results indicate that elevational shift rates are associated with species’ traits, particularly body size, dispersal ability, and territoriality. However, these effects vary substantially across sites, suggesting that responses of tropical montane bird communities to climate change are complex and best predicted within the local or regional context.